Effect Firm Size, Profitability and Inventory Intensity Against Effective Tax Rate (ETR) - Ida Ayu Made Asvini Gita; I D M Partika; D P Suciwati (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
The effective tax rate is the real rate that apply to the taxpayer's income. This research to find out how much influence firm size, profitability, inventory intensity on the effective tax rate of manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. The types of data used are quantitative data and data sources are secondary data in the form of annual financial reports of manufacturing companies in the reporting period at 2015 to 2019. The sample selection used a purposive sampling method with 53 companies and a total of pool data are 202 data. The data analysis method used is multiple regression analysis. The results of this research indicate that profitability had a positive and significant effect on the effective tax rate, inventory intensity had a significant negative effect on the effective tax rate, while firm size had a negative effect on the effective tax rate.